2019
DOI: 10.3390/molecules25010072
|View full text |Cite
|
Sign up to set email alerts
|

Griseaketides A–D, New Aromatic Polyketides from the Pathogenic Fungus Magnaporthe grisea

Abstract: Magnaporthe grisea is the causal agent of rice blast disease, which is the most serious disease of cultivated rice. Aromatic polyketides are its typical metabolites and are involved in the infection process. In the search for novel lead compounds, chemical investigation of the fungus M. grisea M639 has led to the isolation of four new aromatic polyketides (salicylaldehyde skeleton bearing an unsaturated side chain), griseaketides A–D (1–4), as well as 15 known compounds (5–19). The structures of the new compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…7A ). It is also reported that other pyriculol analogs, griseaketides, are produced by a rice blast fungus isolate (Yang et al, 2019 ). Pyriculols are classified into two groups: aldehyde-type (pyriculol and pyriculariol) and alcohol-type (dihydropyriculol and dihydropyriculariol).…”
Section: Pyriculols: Phytotoxic Polyketide Compoundsmentioning
confidence: 97%
“…7A ). It is also reported that other pyriculol analogs, griseaketides, are produced by a rice blast fungus isolate (Yang et al, 2019 ). Pyriculols are classified into two groups: aldehyde-type (pyriculol and pyriculariol) and alcohol-type (dihydropyriculol and dihydropyriculariol).…”
Section: Pyriculols: Phytotoxic Polyketide Compoundsmentioning
confidence: 97%
“…Because ATPase β subunit 471R is relatively conserved in different nematodes, 122 may be a potential broad-spectrum nematicidal compound. 53 ( R )-pyricuol 124 was isolated from rice blast fungus Magnaporthe grisea and could kill 94.5% of C. elegans at 400 μg mL −1 over 24 h. 54 A novel compound, phelligridin L 125 , and the known metabolites 3,14′-bihispidinyl 126 and hispidin 127 were identified from the fungus Sanghuangporus sp. They exhibited activity against C. elegans with LD 50 values of 12.5–50 μg mL −1 at 18 h. 55 An active compound, αβ-dehydrocurvularin (αβ-DC) 128 , was isolated from Aspergillus welwitschiae ; it exhibited activity against Meloidogyne graminicola , a plant root-knot nematode.…”
Section: Structures and Nematicidal Activitymentioning
confidence: 99%
“…The main analogs are dihydropyriculol [ 24 ], pyriculariol [ 25 ], and dihydropyriculariol [ 26 ] ( Figure 3 ). It is also shown that griseaketides, analogs of pyriculol, are produced by an isolate of rice blast fungus [ 27 ]. Pyriculols are classified into two groups: Alcohol-type (dihydropyriculol and dihydropyriculariol) and aldehyde-type (pyriculol and pyriculariol).…”
Section: Pyriculolsmentioning
confidence: 99%